DOES HYPERURICEMIA INFLUENCE ON EFFICACY OF RADIOFREQUENCY SYMPATHETIC DENERVATION OF THE RENAL ARTERY?. (June 2018) - Savelyeva, N.; Gapon, L.; Kuznetsov, V.; Kolunin, G.; E.Mikova,; Krinochkin, D.; Zherzhova, A.; Ulyanov, A.
Abstract : Objective: Hyperuricemia is a risk factor for chronic renal insufficiency and is frequently encountered in patients with arterial hypertension (AH). However the impact of hyperuricemia on efficacy of radiofrequency sympathetic denervation (RFD) of the renal artery in patients with resistant AH (RAH) has not been fully appreciated. The objective of the study was to assess the efficacy of RFD of the renal artery in patients with RAH and hyperuricemia one year after the procedure. Design and method: 15 patients with RAH and hyperuricemia were examined while a comparison group consisted of 12 patients with RAH and without hyperuricemia. All patients received five antihypertensive drugs including diuretics. At baseline and one year after RFD of the renal artery the following parameters were assessed: 24-hour blood pressure monitoring, glomerular filtration rate (GFR) based on Modification of Diet in Renal Disease (MDRD) equation, 24-hour microalbuminuria and left-ventricular myocardial mass index (LVMMI). Results: In one year after RFD of the renal artery the significant decrease in mean 24-hour systolic and diastolic BP was detected in both groups according to 24-hour blood pressure monitoring. GFR level significantly decreased in main group of patients. No changes in microalbuminuria were found. LVMMI did not reach significant differences in patients with RAH and hyperuricemia while significant decrease was observed in a comparison group. Conclusions: In patients with RAH and hyperuricemia one year after RFD of the renal artery along with identical hypotensive effect the significant reduction in GFR was observed. Moreover, no decrease in LVMMI was detected that might be caused by a latent kidney disease providing additional factors for maintenance of AH.